2011
DOI: 10.3109/09637486.2011.618825
|View full text |Cite
|
Sign up to set email alerts
|

Risk and predictive factors of hypoalbuminemia in cancer patients following extensive abdominal surgery despite total parenteral nutritional support

Abstract: Postoperative hypoalbuminemia is associated with adverse outcomes, particularly in cancer patients. The risk and predictors of hypoalbuminemia in cancer patients following extensive abdominal surgery (EAS), despite total parenteral nutrition (TPN) support, were evaluated. A prospective cohort study (n = 115) was conducted in patients with gastrointestinal and/or urogenital malignancies following extensive (n = 81) or moderate (n = 34) abdominal surgery (mean age ± standard deviation: 66.0 ± 11.7 years). EAS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…Fasting, reduced protein-calorie intake, and increased catabolic activity triggered by the stress of surgery are reflected in the decrease in analytical parameters such as urea and serum proteins. This decrease seems to be directly related to the degree of surgical stress to which the patient is subjected [26,27]. In our study, we only observed differences in glucose, urea, and zinc postoperative laboratory parameters between the PPN and FT groups in the short-term follow-up.…”
Section: Discussioncontrasting
confidence: 43%
“…Fasting, reduced protein-calorie intake, and increased catabolic activity triggered by the stress of surgery are reflected in the decrease in analytical parameters such as urea and serum proteins. This decrease seems to be directly related to the degree of surgical stress to which the patient is subjected [26,27]. In our study, we only observed differences in glucose, urea, and zinc postoperative laboratory parameters between the PPN and FT groups in the short-term follow-up.…”
Section: Discussioncontrasting
confidence: 43%
“…But these intraoperative associated factors are not different between the two groups. 9 In this study a total of 204 patients had dilated common hepatic ducts preoperatively, defined as the diameter more than 1cm, measured at the level of 1cm below the bifurcation on CT or MRI scans. And the dilation can reduce the risk of HJ-leak, because the large diameter biliary duct can make the anastomoses technically easier.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have concluded that early post-operative hypoalbuminemia is associated with the pre-operative serum albumin level, age, and extent of surgery [ 12 ], while other studies have shown that post-operative hypoalbuminemia may lead to unfavorable short-term prognoses, such as acute kidney injury [ 13 , 14 ], unbalanced substance metabolism [ 15 17 ], and surgical site infections [ 18 , 19 ]. Such findings suggest that albumin has a role in immune-inflammatory reactions [ 11 , 20 ].…”
Section: Introductionmentioning
confidence: 99%